High-throughput analysis of photocatalytic reactivity of differing TiO2 formulations using 96-well microplate reactors. (May 2019) - Bi, Yuqiang; Westerhoff, Paul
Abstract: The rapid development of photocatalysts for water decontamination benefits from availability of sensitive platforms for screening photocatalytic reactivity. The standard approach typically involves quantifying the degradation of a single dye compound in a slurry system in individual beakers, which requires tedious photocatalyst separation and long operation time. We present a simple and efficient method for assessing the photocatalytic activity of different photocatalyst nanomaterials that eliminates the solid separation process. The 96-well microplate method demonstrated an improved applicability as a high-throughput screening method for photocatalytic reaction mechanisms using a wide range of chemical substrates (i.e., methyl orange, methylene blue, terephthalic acid, and β-nicotinamide adenine dinucleotide coenzyme) and photocatalyst concentrations (1–100 mg/L). By employing photocatalysts at lower concentrations compared to the slurry system, rapid screening was accomplished through direct spectrophotometric or spectrofluorometric measurements. The mass-normalized rate constants of dye degradation were used to determine the photocatalytic reactivity of three commercial TiO2 nanomaterials, which followed an order of SRM TiO2 1898 ≈ Degussa TiO2 P90 > Food-grade TiO2 E171. The extent of hydroxyl radical involvement in methyl orange degradation was estimated to be ∼74% by using radical scavengers in the microplate reactor. Given the utilization of low-concentration photocatalyst, this protocol may be used for evaluating photocatalytic reactivity and oxidative stress caused by photocatalyst exposure in an aquatic environment. We further evaluated photocatalytic reaction kinetics with respect to energetic and photonic efficiency. The method could greatly facilitate comparisons across different laboratories when quantifying photocatalytic reactivity and efficiency, which would aid in standardizing bench-scale photocatalysis testing. Graphical abstract: Image 1 Highlights: High-throughput method enables five-to ten-fold faster screening of photocatalysts. The method employs 96-well microplates with spectrophotometry or spectrofluorometry. Eliminating solid separation process facilitates screening of photocatalytic activity. Substrate degradation mechanisms are evaluated with radical scavengers and probes.